Pengembangan Bahan Ajar Menulis Cerita Pendek Berbasis Multikultural untuk Meningkatkan Pemahaman Nilai-Nilai Budaya Lokal pada Siswa Kelas XI Sekolah Menengah Atas Nurul Ittihadiyah Lubuk Pakam - Sri Lestari; Liesna Andryani; Rika Kartika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The declining awareness of local cultural values among students, coupled with the limited availability of culturally responsive instructional resources, highlights the need for innovative teaching materials in Indonesian language learning. This study aimed to develop multicultural-based short story writing teaching materials and evaluate their feasibility and effectiveness in enhancing students’ understanding of local cultural values. The research employed a Research and Development approach using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The participants were eleventh-grade students of Nurul Ittihadiyah Senior High School, Lubuk Pakam, Indonesia. Data were collected through observations, interviews, questionnaires, and learning outcome tests. The findings revealed that the developed teaching materials achieved a very high level of feasibility based on evaluations conducted by material and media experts. Students also demonstrated positive responses toward the instructional materials, indicating their practicality and attractiveness in the learning process. Furthermore, the implementation of the teaching materials contributed to improved understanding of local cultural values and enhanced short story writing skills. These findings affirm that multicultural-based teaching materials constitute an effective instructional resource for integrating cultural literacy and writing competence in Indonesian language education.